STUDYING THE EFFECTIVENESS OF MONOCLONAL ANTIBODIES AGAINST CORONAVIRUS INFECTION - Agzamkhodjaeva Nozimakhon Ulugbekovna; Islamova Rano Karimdzhanovna (Scholar Express Journals, 2024)
Monoclonal antibodies (mAbs) have emerged as a promising therapeutic option for the prevention and treatment of coronavirus infections, particularly COVID19 caused by the SARS-CoV-2 virus. These laboratory-made proteins target specific components of the virus, preventing viral entry into human cells and subsequent replication. Clinical trials and real-world evidence have demonstrated the efficacy of monoclonal antibodies in reducing the severity of COVID-19 symptoms, decreasing the risk of hospitalization and death, and providing immediate protection against the virus through passive immunization.
Keywords: Monoclonal antibodies; Coronavirus; SARS-CoV-2